Microstructural and mechanical analysis on Cu–Sn intermetallic micro-joints under isothermal condition. (November 2015) - Mo, L.; Chen, Z.; Wu, F.; Liu, C.
Abstract: This study focuses on the mechanism of phase transformation from Cu6 Sn5 into Cu3 Sn and the homogenization process in full intermetallics (IMCs) micro-joints, which were prepared by soldering the initial Cu/Sn/Cu structure through high temperature storage in vacuum environment as the Transient Liquid Phase (TLP) process. From the microstructural observation by electron backscatter diffraction (EBSD), a mixture of IMCs phases (Cu6 Sn5 and Cu3 Sn) has been found to constitute the sandwich-structured Cu/IMCs/Cu joints. With the dwell time increasing at 533 K, there were two layers of Cu3 Sn emerging from both sides of copper substrates with the depletion of Cu6 Sn5 layer, toward merging each other in the IMCs interlayer. Then the Cu3 Sn grains with various sizes became more homogenous columnar crystallites. Meanwhile, some equiaxial ultra-fine grains accompanied with the Kirkendall voids, were found only in adjacent to the electroplated copper. In addition, a specific type of micropillar with the size ∼5 μm × 5 μm × 12 μm fabricated by focus ion beam (FIB) was used to carry out the mechanical testing by Nano-indentation, which confirmed that this type of joint is mechanically robust, regardless of its porous Cu3 Sn IMC interconnection. Highlights: Entire Cu–Sn IMCs joint has been prepared through TLP soldering at 533 K. Different microstructure as Cu6 Sn5 surrounding Cu3 Sn phase was observed. Flux-driven ripening process of Cu3 Sn IMC joint was revealed through EBSD results. Microstructural evolution of Cu–Sn IMCs joints was demonstrated systematically. Porous Cu3 Sn IMC joint was confirmed to be mechanically robust.